2014
DOI: 10.1007/s11764-014-0370-6
|View full text |Cite
|
Sign up to set email alerts
|

Health status, use of healthcare, and socio-economic implications of cancer survivorship in Portugal: results from the Fourth National Health Survey

Abstract: Our study provides valuable information for understanding the global impact of cancer survivorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
2
9
1
Order By: Relevance
“…Although organized cancer screening programs in Northern Portugal are relatively recent [39], a previous study based on a representative sample of the adult Portuguese population showed a high use of breast, cervical and prostate cancer screening [40]. Additionally, as cancer screening is more frequent among cancer survivors than in the general population [41,42], a high frequency of these cancers as SPCs may be expected. Nevertheless, our results essentially reflect the fact that these cancers have some of the highest incidence rates and no increased incidence was observed in comparison with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Although organized cancer screening programs in Northern Portugal are relatively recent [39], a previous study based on a representative sample of the adult Portuguese population showed a high use of breast, cervical and prostate cancer screening [40]. Additionally, as cancer screening is more frequent among cancer survivors than in the general population [41,42], a high frequency of these cancers as SPCs may be expected. Nevertheless, our results essentially reflect the fact that these cancers have some of the highest incidence rates and no increased incidence was observed in comparison with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of incident cases of cancer [1] and the improvements in survival [2] have been contributing to a growing population of subjects with a previous diagnosis of cancer. It was estimated that in 2012, there were more than 32 million cancer survivors worldwide [3]; these subjects have an increased risk of several adverse health events and use of health resources [4], including the recurrence of the first primary cancer (FPC), cardiovascular diseases or second primary cancers (SPC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients did not report less income than controls, since they all had health insurance, and most were retired at the time of the study. The financial situation for French cancer survivors seems to be more preserved than in the United States (Whitney et al., 2016), Portugal (Pacheco‐Fig ueiredo & Lunet, 2014) or Norway (Syse & Tønnessen, 2012). An American prospective survey showed a negative impact of financial burden on cancer survivors' quality of life (Zafar et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…LC were evaluated by a questionnaire developed in 1995 by the General Calvados cancer registry, already used in many studies and adapted for QALIPRO in 2011 (Joly et al, 1996(Joly et al, , 2002. It has 58 items and gathers socio-demographic characteristics at the time of diagnosis and 10 years after.…”
Section: Living Conditions Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation